2012
DOI: 10.1016/j.ydbio.2011.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger homeobox is required for the differentiation of serotonergic neurons in the sea urchin embryo

Abstract: Serotonergic neurons differentiate in the neurogenic animal plate ectoderm of the sea urchin embryo. The regulatory mechanisms that control the specification or differentiation of these neurons in the sea urchin embryo are not yet understood, although, after the genome was sequenced, many genes encoding transcription factors expressed in this region were identified. Here, we report that zinc finger homeobox (zfhx1/z81) is expressed in serotonergic neural precursor cells, using double in situ hybridization scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…MO, morpholino. (Yaguchi et al, 2012(Yaguchi et al, , 2008(Yaguchi et al, , 2010. The formation of serotonergic neurons begins during the early pluteus larval stages on the dorsal side of the embryo in a territory around the interface of the inner anterior discoidal domain marked by foxq2 expression and the outer ANE domain marked by the ring of six3 expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MO, morpholino. (Yaguchi et al, 2012(Yaguchi et al, , 2008(Yaguchi et al, , 2010. The formation of serotonergic neurons begins during the early pluteus larval stages on the dorsal side of the embryo in a territory around the interface of the inner anterior discoidal domain marked by foxq2 expression and the outer ANE domain marked by the ring of six3 expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression patterns of six3 and foxq2 at the mesenchyme blastula stage (24 hpf ) and the fact that FoxQ2 acts as a cardinal regulator of many cell fates in the central ANE territory (Yaguchi et al, 2012(Yaguchi et al, , 2011(Yaguchi et al, , 2010, we reasoned that FoxQ2 might play a crucial role in establishing the inner and outer ANE domains. To test this hypothesis, we monitored the expression of six3 at the mesenchyme blastula stage in embryos injected with FoxQ2 morpholino oligonucleotides.…”
Section: Two Concentric Ane Territoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although another zinc finger protein, Zfhx/Z81 (Yaguchi et al, 2012), has been shown to be required for the development of serotonergic neurons, and several other transcription factors have been shown to be expressed within them , Z167 is the first factor to be shown to functionally link to the shared core regulatory pathway of Six3→SoxC→Brn1/2/4 that is required for all neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of a number of genes implicated in neurogenesis in other systems have been identified that also depend on Six3 for expression (Wei et al, 2009) and the requirement for several has been demonstrated by functional assays, including Zfhx for serotonergic neurons (Yaguchi et al, 2012) and Nkx3.2 for pharyngeal neurons (Wei et al, 2009). Here, we have provided a scaffold pathway for integrating other genes into a GRN for neurogenesis in sea urchin embryos.…”
Section: Discussionmentioning
confidence: 99%